“I STAND ON THE RIGHT SIDE”: A WAR OF SOCIAL MEDIA AVATARS IN THE 2014 INDONESIAN PRESIDENTIAL ELECTION CAMPAIGN - Gunawan, Iwan; Alkatiri, Zeffry; Aji Wibowo, FX. Catur Satria (International Review of Humanities Studies, 2021)
The development of social media in the realm of democracy through internet technology has been used by numerous groups for various purposes. A number of software programs with their applications make it easier for someone to produce countless content on social media. One of the functions of such programs is to create different images in relation to the 2014 Indonesian presidential election. In the 2014 presidential election, there was a rivalry between the two groups of voters who attacked each other using various image products through social media. Those supporting Joko Widodo (Jokowi) created a campaign image in the form of an avatar template containing the number “2” with the words "I Stand on the Right Side". The image then went viral and was responded to by the voters for the presidential candidate Prabowo Subianto with a variety of contending images. This research documents and analyzes the various images created and circulated during the 2014 Indonesian presidential election, as well as reconstructing the conflict between the two groups of voters in the presidential election in the context of Indonesian democracy, which was still in its development. Data was collected from various websites and social media from May to October 2017. This research was conducted through historical methods. Meanwhile, in examining the various images, this research used a visual communication approach to graphic design.